Dreams are made of memories, but maybe not for memory - Mark Blagrove (Behavioral and Brain Sciences, 2013)
Llewellyn's claim that rapid eye movement (REM) dream imagery may be related to the processes involved in memory consolidation during sleep is plausible. However, whereas there is voluntary and deliberate intention behind the construction of images in the ancient art of memory (AAOM) method, there is a lack of intentionality in producing dream images. The memory for dreams is also fragile, and dependent on encoding once awake.